The Physiochemical Properties of Wells Water in Alboalwan Region /Alanbar Province / Iraq. - AL-Alwani, A.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The physiochemical properties are considered to be as important guidelines for quality of water and their use for social, agricultural and different ecological applications. Fourteen properties were investigated in this study, including (PH, Electrical Conductivity (EC), Total Dissolved Salts(TDS), Turbidity,Total Hard ness(TH),Sodium(Na),Calcium(Ca),Magnesium(Mg),Carbonate(CO3),Chloride (Cl),Phosphate(PO4),Nitrite(NO2),Nitrate(NO3),and Sulphate(SO4) for the wells water at Albualwan region in Al - Anbar province east of Iraq . The results showed that the studied properties recorded values since were (7.3,2230.5Ms,869.5ppm,0.32NTU,521.31ppm,3.6grŁ,111.5ppm,139.05ppm,296.86ppm, 116 .6ppm,0.42ppm,0,02ppm,4.7ppm and 440.5ppm) respectively. Also the results indicated that most of the properties specially (EC,TDS,TH,Na, ,Mg,NO2,NO3, and SO4 ) were higher than the accepted values by WHO. So it’s necessary to be aware of the problems which these waters may cause when used for human drinking